Experimental Pharmacological Research Regarding the Potential Antidepressant Activity Induced by Some Newly Synthesised Dibenzo[a,d]cycloheptene Compounds - Emil Ștefănescu; Corina Scutari; Ioana Păunică; Adrian Junghină (Journal of Mind and Medical Sciences, 2015)
Background. Depression is a relatively frequent encountered mental disorder in the general population, affecting both the quality of the individual life and its ability to perform the social tasks; it is generally accepted that new studies related to this pathologic condition are further necessary, in order to identify more adequate, efficient and accessible therapeutic compounds. Materials and methods. This study was performed on a sample of 60 white male mice, NMRI strain, who were divided into 6 groups of 10 animals and treated with 4 new derivatives of dibenzo [a, d] cycloheptene, amitriptyline as a reference substance, or with distilled water for the control group. The animals were tested in respect to the forced swim test, both before and at 2 hours after administration of the mentioned substances. It was determined thus the time of immobilization. Results. The study showed the fact that only two of the four investigated compounds presented a relatively similar antidepressant effect with the reference substance. Conclusions. Minor structural changes, such as modifications of some substitutes from the basic chemical core of the reference substance can decisively influence the conservation or loss of the antidepressant properties.